2020
DOI: 10.1080/2162402x.2020.1758003
|View full text |Cite
|
Sign up to set email alerts
|

ROS1-fusion protein induces PD-L1 expression via MEK-ERK activation in non-small cell lung cancer

Abstract: Introduction: Despite some of the oncogenic driver mutations that have been associated with increased expression of programmed death-ligand 1 (PD-L1), the correlation between PD-L1 expression and ROS1 fusion in NSCLC cells, especially for those with Crizotinib resistance has not been fully addressed. Materials and Methods: The expression of PD-L1 in 30 primary NSCLC tumors with/without ROS1fusion protein was evaluated by immunohistochemical (IHC) analysis. To assess the correlation between ROS1 fusion and PD-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…In our work, PD-L1 expression in HCC1937 and HCC1806 was significantly increased after combined treatment, but diminished in MDA-MB-231 and HCC1806 cells after single treatment with the ERK inhibitor. In concordance, Qian and colleagues showed a decreased PD-L1 mRNA expression after ERK1/2 inhibition in bladder cancer cells (Qian et al 2008), and Liu and coworkers confirmed a downregulation of PD-L1 expression and ERK phosphorylation in NSCLC cells after PD0325901 or U0126 treatment (Liu et al 2020). Several studies indicated an increased PD-L1 expression in TNBC compared to non-TNBC, though the results differed strongly (Barrett et al 2015;Bedognetti et al 2016;Gatalica et al 2014).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In our work, PD-L1 expression in HCC1937 and HCC1806 was significantly increased after combined treatment, but diminished in MDA-MB-231 and HCC1806 cells after single treatment with the ERK inhibitor. In concordance, Qian and colleagues showed a decreased PD-L1 mRNA expression after ERK1/2 inhibition in bladder cancer cells (Qian et al 2008), and Liu and coworkers confirmed a downregulation of PD-L1 expression and ERK phosphorylation in NSCLC cells after PD0325901 or U0126 treatment (Liu et al 2020). Several studies indicated an increased PD-L1 expression in TNBC compared to non-TNBC, though the results differed strongly (Barrett et al 2015;Bedognetti et al 2016;Gatalica et al 2014).…”
Section: Discussionmentioning
confidence: 82%
“…Downregulation of PD-L1 with siRNA was accompanied by downregulation of mesenchymal proteins and decreased phosphorylation of ERK and STAT3 (Cui et al 2021 ). Also, ERK mediates PD-L1 expression in NSCLC (non small cell lung carcinoma) cells with ROS1 fusion: Liu and coworker showed that both ERK phosphorylation and PD-L1 expression were down-regulated after treating HCC78 cells with PD0325901 or U0126 (Liu et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Non-crizotinib systemic therapies yielded mixed results within this cohort. Despite a high rate of PD-L1 expression reflecting a known association between ROS1-rearrangements and upregulated PD-L1 [29], response to and effectiveness of ICI in this cohort was limited, with outcomes significantly below those observed in similarly treated, but driver-mutation negative KEYNOTE-42 and 189 cohorts [30,31]. These findings support an emerging body of literature suggesting that ICI use-particularly ICI monotherapy-in ROS1-rearranged NSCLC may elicit an inconsistent and generally poor response [32], implying that PD-L1 expression alone may not be sufficient to predict response to ICI, especially in the presence of a driver mutation [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggests that PD-L1/PD-1 blockade could be the second-line treatment option based on the correlation of ROS1 fusion with PD-L1 expression. 4 Two patients with ROS1 fusion have been reported to respond well to immunotherapy. 16 However, PD-L1 expression was upregulated in this ROS1 -rearranged NSCLC patient after ceritinib treatment but did not bring about a long-term benefit from ICT.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Nonetheless, studies have demonstrated the correlation between ROS1 rearrangement and high programmed cell death ligand 1 (PD-L1) expression. 4 5 Whether ICI-based therapy is effective in patients following first-line targeted agents still needs more investigation.…”
Section: Introductionmentioning
confidence: 99%